Effectiveness of SCRUM in project based learning: Students view - Dinis-Carvalho, José (2019)
Project and team management play a major role in the student team’s project performance. This is more evident when projects last a long time and the teams are large. In this work, a student team accepted to use SCRUM as their project management methodology during their Project Based Learning (PjBL) experience. This PjBL experience took place on the 7th semester of the Integrated Master in Industrial Engineering and Management degree. The team had a short period of time to train the technique and apply it throughout the entire semester. Although not very enthusiastic in the beginning of the project, the team gradually became aware of the advantages of SCRUM features, recognizing the feeling of having the project under control and gaining management effectiveness throughout the semester. In the end, the team performed well above the average, being one of the two teams with the highest score of the class.